PENGUATAN MODAL SOSIAL BERBASIS KELEMBAGAAN LOKAL MASYARAKAT PESISIR PERSPEKTIF GENDER DI KABUPATEN BANTUL - Oktiva Anggraini; Muhammad Agus (University of Jember, 2018)
The aims of this research are getting to know: encouraging the creation of social capital empowerment in the empowerment of fisherman based local institution with gender perspective in coastal area of ​​Bantul regency. With descriptive qualitative research design, data collection techniques: in-depth interview; literature study, observation and FGD. The results showed that coastal villages in Bantul district have developed institutions and rules that effectively limit the rate of exploitation of natural resources. Characteristic of social capital of coastal community in research location indicated that dominant group is group of citizen (arisan, RT), pengajian, fisherman group and fisherman. Given that the dominant group resides in the internal environment of the settlement and consists of the settlement community itself, access to outside resources is limited. The level of participation in the group was quite good seen from the presence, material and non-material. The level of trust and solidarity is relatively high. Values ​​are still firmly held and result in collective action and cooperation is relatively good enough. Social capital was more used for the fulfillment of daily needs (subsistence), is temporary and very personal. There was still a less supportive local culture, a wasteful life. Not many types of services could be expanded access because of the existence of a limited group. Social capital that supports the management of tourist destinations and coastal community empowerment in general need strengthening of related institutions, especially DKP, Dinpar and Disperindagkop Bantul regency more integrated. The caution of the coastal empowerment initiators resulted in coastal communities in Bantul district failing to develop social capital in the context of managing government resources such as bangdes funds, etc